Woman as culture-bearer in Magdalena Jalandoni's three selected novels - Gonzales, Alicia Tan (Danyag :the UPV journal of humanities and social sciences, 2008)
"This study is delimited to Jalandoni's three most popular novels namely "Ang Bantay sang Patyo" (1923), "Ang Dalaga sa Tiendahan" (1934), and "Juanita Cruz" (1965). It interrogates the gender ideology of the specific cultural formation depicted in the novels and how this ideology possibly reinforced the power structures of the social formation during the time that she wrote. Jalandoni's works represent women as moral exemplars, reinforcing the norms of female conduct stipulated by the patriarchal ideology deeply embedded in the teachings of the Catholic Church. We see a hierarchy of values that govern female conduct: honoring of one's parents and the virtue of chastity, both of which find their equivalent in the Ten Commandments; and erotic love, which finds consummation only in the sacrament of marriage. Moreover, this study notes how some of the women protagonists of Jalandoni's works, despite being caught in a web of relations governed by patriarchy (i.e., as anideology), manage to negotiate their subject positions within a cultural formation informed by the norms of behavior stipulated by the Catholic Church during the Spanish Colonial Period, thus earning them a quantum of freedom."